STUDY OF PRODUCTION OF REVERSE OSMOSIS DEMINERALIZED WATER FOR BOILERS - ROVANI, MICHELLE ZANIN; SAVI, LIZANDRA KAMRADT; MAFRA, LUCIANA IGARASHI; DEMIATE, IVO MOTTIN (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2017)
A comparison of the presence and absence of a softening system as a pretreatment of the water that is fed into the separation process by reverse osmosis membranes was performed. The following parameters of the reverse osmosis were evaluated: the pH of the feed water; the flow of the permeate; the pressure of the feed water in the membrane in the first and second stages; and the pressure of the reject, both in the absence and the presence of the softening system. The results indicated that the inclusion of a softening system as a pretreatment for feeding the reverse osmosis process prevented the premature deposition of silica, thereby increasing the useful life of the membranes